Enablers and constraints influencing implementation of a novel, multi-site community-based frailty programme: perspectives of leaders and implementers - Poh Hoon June Teng; Hwee Teng Robyn Tan; Ngoc Huong Lien Ha; Wee Shiong Lim; Yew Yoong Ding; Woan Shin Tan; Geriatric Services Hub Programme Group (BMC Geriatrics)
Abstract Background Evaluations of integrated care models for frailty anchored by comprehensive geriatric assessment have reported mixed effects on patient outcomes. Various reasons have been proposed, including how implementation varies widely across different contexts. This paper aims to identify the key enablers and constraints that influenced the implementation of a novel community-based frailty programme– the Geriatric Services Hub– in the rapidly ageing nation-state of Singapore through the perspectives of programme leaders and implementers from five sites. Methods Seventy-four programme leaders and implementers were recruited for in-depth interviews and focus group discussions. The Framework Method was used to summarise and compare data across different sites and perspectives. Results The findings on enablers and constraints were organised into four domains: System, partnership, programme and patient factors. Systemic factors include differing subsidies across public and private healthcare providers, systemic constraints of primary-care partners, a fragmented system of care, and the COVID-19 pandemic. Partnership factors include how capability-building for primary-care and community partners was welcomed by stakeholders. At the programme level, ensuring physical, financing, and timely access to services by frail older adults was prioritised. However, as noted under patient factors, some GSH patients faced complex medical, social, and financial issues that may affect service utilisation. Conclusions Systemic factors had a major influence on the implementation of GSH and we posit that they hold particular relevance for integrated care models in complex healthcare systems. Whole-system changes above and beyond implementation efforts of individual programmes may be needed for successful and sustainable implementation of integrated care.